Impact of community based breeding program on breeding buck availability, growth and reproductive performance of Black Bengal goat - Solaiman, M; Apu, AS; Ali, MY; Fakruzzaman, M; Faruque, MO (Bangladesh Journal of Animal Science, 2020)
The present study was undertaken to evaluate the availability of breeding bucks as well as growth and reproductive performances of Black Bengal goat under community based breeding program. A total of 30 goat rearers in three areas of Sakhipur upazilla were selected based on the survey result. Selected goat rearers were trained on scientific rearing, management and community-based breeding of Black Bengal goat and also build up community link with them. Three Black Bengal breeding bucks have been distributed among three potential farmers in three villages under Sakhipur upazilla. The management and performance of Black Bengal goats were monitored closely and analyze the impact of community based breeding program. The analysis of the growth performance showed that male kids attained significantly (p<0.05) higher birth weight (1.28±0.04 kg) than that of female kids (1.06±0.02 kg). The body weights of male at 3, 6, 9 and 12-month were 5.41±0.28, 9.18±0.32, 12.87±0.35 and 16.91±0.46 kg whereas female reached significantly (p<0.05) lower body weight as 4.97±0.16, 8.02±0.21, 10.91±0.23 and 14.21±0.34 kg at the same ages, respectively. Average daily body weight gain up to 12 months of age was also significantly (p<0.05) higher in males (43.42±1.17 g/day) than females (36.53±2.49 g/day). On the other hand, season had a significant effect (p<0.05) on the body weights of Black Bengal goat at 0 (birth), 3, 6, 9, 12-month of age. In case of reproductive performances, it was revealed that age at sexual maturity was 199.32±2.41 days; age at first kidding 393.23±1.38 days; service per conception 1.17±0.04, and litter size was 1.76±0.08 in community based breeding program. Beside these, post-partum heat period of Black Bengal goat was found 47.50±0.87 days. Comparing with the findings of previous research works, these results suggested that community based breeding program has not only reduced the scarcity of good quality breeding bucks but also improved the growth and reproductive performances of Black Bengal goats. Bang. J. Anim. Sci. 2020. 49 (1): 13-21